2021
DOI: 10.1108/ijoem-09-2020-1146
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and financial performance of banks in Ghana: the moderating role of ownership structure

Abstract: PurposeThe purpose of this paper is to investigate the moderating effect of ownership on the links between corporate governance and financial performance in the context of Ghanaian banks.Design/methodology/approachThe current study used a sample of 23 banks and the multiple regression method to analyze a panel dataset of 414 from banks over an 18-year period.FindingsThe findings revealed that audit independence, chief executive officer (CEO) duality, non-executive directors and banks size have a positive impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 107 publications
5
39
0
4
Order By: Relevance
“…In this context, many studies emphasized the impact of governance structures on the financial performance of companies and their profitability (Musah & Adutwumwaa, 2021;Boachie, 2021). Meanwhile, some other studies have shown a relation between governance and the financial and operational performance of companies in various sectors (Aslam et al, 2021;Nasrallah & El Khoury, 2022).…”
Section: Third: the Strategy Of Governancementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, many studies emphasized the impact of governance structures on the financial performance of companies and their profitability (Musah & Adutwumwaa, 2021;Boachie, 2021). Meanwhile, some other studies have shown a relation between governance and the financial and operational performance of companies in various sectors (Aslam et al, 2021;Nasrallah & El Khoury, 2022).…”
Section: Third: the Strategy Of Governancementioning
confidence: 99%
“…Moreover, the need for adopting a risk-based approach in companies during the past decade has led to an increased interest in defining and evaluating risks and taking them as guidance in making decisions related to the company (Khorin, & Krikunov, 2021). Some changes must be made in the organizational structures in companies so that investors become more sensitive to the volatility of profits as a result of exposure to risks (Boachie, 2021;Grabinska et al, 2021). Meanwhile, some other studies have concluded that the increase in the accountability rules within the governance of boards of directors and the existence of specialized committees in risk management contribute significantly to focus on the risk management systems and getting tangibly close to the capital and insurance markets (Alareeni & Hamdan, 2020;Lee & Suh, 2022).…”
Section: Second: the Reputational Risksmentioning
confidence: 99%
“…Researches have proven that, good CG may have positive impact on SME performance (Abor & Biekpe, 2007). Boachie (2021) assessed the mediating role of ownership on the nexuses between CG and BP of banks in Ghana. Deploying a multiple linear regression methodology on a panel data set of 414 observations on 23 banks over an eighteenyear period, the study found that, audit independence, CEOD, non-executive directors and banks size depicted a positive effect on BP.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Ofoeda (2017) also investigated the influence of CG mechanisms of non-bank financial institutions (NBFIs) on their profitability in Ghana. Boachie (2021) assessed the mediating role of ownership on the nexuses between CG and BP of Ghanaian banks; Musah and Adutwumwaah (2021) assessed CG mechanism influence on the BP of Ghanaian rural banks; Gakpo and Kwakye (2021) conducted a study to find out whether good CG practices adherence affects Ghanaian State-Owned Enterprises (SOEs) financial performance among other studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation